Понятие и основания правового контрактивизма - Юдін, Зореслав Михайлович; Юдин, Зореслав михайлович; Judin, Zoreslav (My University, 2011)
The selection of its qualitatively new attributes, by which a new definition of the contract is proposed. Justified that the contract as a general legal category is the center of the entire sphere of phenomena and processes in the legal reality. For its systematic researching suggested the allocation of separate sphere of knowledge about the law — contrantivistics.
Юдин З. М. Понятие и основания правового контрактивизма / З. М. Юдин // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 305-312.
Keywords: общетеоретическая юриспруденция; договор; признаки договора; правовой контрактивизм; загальнотеоретична юриспруденція; договір; ознаки договору; правовий конструктивізм; general theoretical law; agreement; signs contract; legal contractualism